2015
DOI: 10.2147/ppa.s93783
|View full text |Cite
|
Sign up to set email alerts
|

The interactive web-based program MSmonitor for self-management and multidisciplinary care in multiple sclerosis: concept, content, and pilot results

Abstract: BackgroundThere is a growing need to offer persons with multiple sclerosis (PwMS) possibilities for self-management and to integrate multidisciplinary health data. In 2009–2014 we developed a patient-reported outcome based, interactive, web-based program (MSmonitor) for (self-)monitoring, self-management and integrated, multidisciplinary care in MS.MethodsThe notions underlying the MSmonitor concept and the program’s elements are described. We analyze MSmonitor’s role in the self-management of fatigue by retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 33 publications
1
43
0
1
Order By: Relevance
“…This suggests that the mere fact of measuring physical activity levels and monitoring fatigue may have a positive effect on perceived fatigue. A similar effect was seen in a study where the use of activity diaries was shown to be a contributor to the selfmanagement of fatigue (Jongen et al, 2015b), and in studies of selfmanagement programs using an interactive web-based program (Jongen et al, 2015a).…”
Section: Discussionsupporting
confidence: 64%
“…This suggests that the mere fact of measuring physical activity levels and monitoring fatigue may have a positive effect on perceived fatigue. A similar effect was seen in a study where the use of activity diaries was shown to be a contributor to the selfmanagement of fatigue (Jongen et al, 2015b), and in studies of selfmanagement programs using an interactive web-based program (Jongen et al, 2015a).…”
Section: Discussionsupporting
confidence: 64%
“…1 Interactive, Web-based, patient-focused programs may enhance self-management and allow for an integrated interdisciplinary approach. Examples include MSmonitor, a program for self-monitoring, selfmanagement, and integrated, multidisciplinary care in MS, 56 and MSInvigor8, a cognitive behavioral therapy self-management program for MS fatigue. 57,58 MSmonitor comprises six validated questionnaires, two inventories (medication and adherence), two diaries, and two functionalities (e-consult and personal e-logbook).…”
Section: Role Of Sdm In Dmd Selection and Adherencementioning
confidence: 99%
“…57,58 MSmonitor comprises six validated questionnaires, two inventories (medication and adherence), two diaries, and two functionalities (e-consult and personal e-logbook). 56 A pilot study using this program suggested that repeated use of the short Modified Fatigue Impact Scale-5-item version and the 8-item Leeds Multiple Sclerosis Quality of Life questionnaire was associated with an increase in health-related quality of life. 56 MSInvigor8 consists of eight tailored, interactive sessions, 57 and a pilot randomized trial demonstrated that addition of e-mail-based support (MSInvigor8-Plus) significantly reduced fatigue severity.…”
Section: Role Of Sdm In Dmd Selection and Adherencementioning
confidence: 99%
“…A separate tool, MSmonitor, is an interactive, Internet-based program for the self-monitoring, self-management, and integrated multidisciplinary care of patients with MS [37]. The original content comprised: (1) questionnaires to assess the impact of MS and related quality of life, fatigue, anxiety, and depression; (2) inventories to capture medication, adherence, and urological symptom data; (3) diaries to record activity, rest periods, micturition, and fluid intake; (4) an "e-consult" functionality to enable patients to contact their physician; and (5) an "e-logbook" [37].…”
Section: Disease Monitoring and Self-managementmentioning
confidence: 99%
“…The original content comprised: (1) questionnaires to assess the impact of MS and related quality of life, fatigue, anxiety, and depression; (2) inventories to capture medication, adherence, and urological symptom data; (3) diaries to record activity, rest periods, micturition, and fluid intake; (4) an "e-consult" functionality to enable patients to contact their physician; and (5) an "e-logbook" [37]. Pilot data suggested that repeated use of MSmonitor led to an increase in health-related quality of life and helped patients to self-manage fatigue [37]. In a subsequent survey of 55 patients with MS, MSmonitor has been shown to improve patients' insights into symptoms and disabilities, and improve the quality of nursing care they received [38].…”
Section: Disease Monitoring and Self-managementmentioning
confidence: 99%